The Biofertilizer Formulation from Coconut Fiber Waste and Oyster Mushroom Waste as Basic Substrate, the Active Agent of Aspergillussp. - Abdul Rahim Thaha, Asrul1,Halmia Umrah (International Journal of Advanced Science and Technology, 2020)
This study on the formulation of waste biofertilizer substrate fromCoconut fiber and active oyster mushrooms Aspergillus sp. The study held at the Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University and in the Langalesovillage, Dolo Sub- District, Sigi District. The chemical analysis carried out in the Laboratory of Soil Science, Faculty of Agriculture, TadulakoUniversity. The study was designed in a completely randomized design (CRD), consists of five treatments and four replications.The composition of the treatmentare: P0 (basic substrate 100%, withoutsupplements), P1 (basic substrate 90% + supplement 10%), P2 (basic substrate 80% + supplement 20%), P3 (basic substrate 70% + supplement 30%) and P4 (basic substrate 60% + supplement40%). Results of invisible observationindicates of biologicalparameters Aspergillus sp. cangrowth and dominatein all media treatment.Observations physical parameters, aromas range from 2.23 to 2.28 (smelly compost), the color range of 1.86 to 2.11 (dark brown-black to black). Observations textures range from 1.61 to 1.81 (medium). Observations chemical analysis showed the lowest C-Organic at P4 (21.98%), the highest nitrogen scores at P1 (0.84%), the highest value of phosphorus (P) at P3 (0.15%), the highest value of potassium at P4 (1.69 %), the highest value of Sodium at P2 (12:32%) and the highest calcium value at P3 (3.00%).